2012
DOI: 10.1111/j.1600-0897.2012.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of Peripheral Blood Natural Killer Cells in Women with Repeated IVF Failure

Abstract: Peripheral blood NK cell activity is significantly higher in women with RIF than in fertile controls. Future trials of immune therapy in women undergoing IVF should target those with high NK activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 34 publications
(44 reference statements)
4
25
1
Order By: Relevance
“…Many studies complement our hypothesis, showing that uNK and T lymphocyte rates are decreased in patients with unknown infertility reporting a dysregulation of cytokines production (Klentzeris et al, 1992;Fukui et al, 2006;Karami et al, 2012;Chernyshov et al, 2010;Sacks et al, 2012;Zhou et al, 2012;Dons'koi et al, 2013a,b). Furthermore, an interesting and recent study demonstrated that PBMCs intrauterine administration had no effect on implantation rate in patients with only one IVF failure (34 vs. 33%) but significantly increased in patients with at least three IVF failures (42 vs. 25%) (Okitsu et al, 2011).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Many studies complement our hypothesis, showing that uNK and T lymphocyte rates are decreased in patients with unknown infertility reporting a dysregulation of cytokines production (Klentzeris et al, 1992;Fukui et al, 2006;Karami et al, 2012;Chernyshov et al, 2010;Sacks et al, 2012;Zhou et al, 2012;Dons'koi et al, 2013a,b). Furthermore, an interesting and recent study demonstrated that PBMCs intrauterine administration had no effect on implantation rate in patients with only one IVF failure (34 vs. 33%) but significantly increased in patients with at least three IVF failures (42 vs. 25%) (Okitsu et al, 2011).…”
Section: Resultssupporting
confidence: 77%
“…Thus immunotherapy appears to be ineffective in patients with RIF caused by an early dysregulation in the maintenance of pregnancy. Patient with unexplained recurrent spontaneous abortions (URSA) probably present with over-activation of cytotoxic uNKs characterized by up-regulation of CD69stim and CD158a as reported elsewhere (Chernyshov et al, 2010;Sacks et al, 2012;Dons'koi et al, 2013a,b;Wu et al, 2014). In these patients, another therapeutic strategy needs to be developed.…”
Section: Resultsmentioning
confidence: 93%
“…However, it is important to note that the sensitivity of this test was only 11% suggesting that women with RIF might have multiple other factors that contribute to their difficulty in achieving pregnancy. Testing NK cell levels therefore cannot necessarily be used to distinguish women with RIF from the general population, but rather might be used in women with already established RIF, to determine whether the etiology of their implantation failure is related to their immunological profile [ 32 ].…”
Section: Pathophysiological Mechanisms Of Recurrent Implantation Failmentioning
confidence: 99%
“…The normal range for NK cell numbers and activity in peripheral blood from normal individuals varies widely, at ∼5–30% of mononuclear cells (Bisset et al , 2004; Sacks et al , 2012). Notably, however, pbNK are never measured routinely in any clinical condition apart from haematological disorders, such as leukaemia, because no clinically useful information is obtained.…”
Section: Nk Testingmentioning
confidence: 99%